STILISTIKA PADA IKLAN PRODUK KECANTIKAN DI YOUTUBE - May Adelia Pramesti; Eko Cahyo Prawoto (Buana Bastra, 2020)
Youtube is one of the facilities of information on social media to air an advertisement. Youtube is visited by many people, especially teenagers. Many advertisements are aired on youtube, one of them is a beauty product advertisement. Beauty products are in high demand by Indonesian women, especially teenagers, because basically women always want to look beautiful. The use of language styles and impressions that we can catch on the beauty products advertisement is one of the things that influences consumers to be interested in buying it. The basis of this research begins with linguistics, namely stylistics. The purpose of this research is to describe more deeply, adequately, and comprehensively about climax language style, hyperbole language style, metaphorical language style and image on beauty products advertisements on youtube. The theory used in this research is stylistic theory. The method used in this research is qualitative method. Data collection techniques using documentation and observation. The data analysis technique used is descriptive data analysis techniques (processing, analyzing, and interpreting data). The results of the research found on the beauty products advertisement on youtube, amounting to 60 products include climax language style, hyperbole language style, metaphorical language style, and imagery (vision and touch). Conclusions and suggestions are given so that this research is useful for other researchers, advertisers, and the society.